See - Mandic, Danilo; Philippopoulos-Mihalopoulos, Andreas; Pavoni, Andrea; Nirta, Caterina (University of Westminster Press, 2018)
Vision traditionally occupies the height of the sensorial hierarchy. The sense of clarity and purity, it is the one most explicitly associated with truth and knowledge. The law has always relied on vision and representation, from eye-witnesses to photography, and more precisely it can be understood as that which decrees what is visible and what is not, through its normative gaze. However, if law's perspectival view is bound to be betrayed by the reality of perception, it is nonetheless productive of real effects on the world. This first title in a new interdisciplinary series 'Law and the Senses' asks how can we develop theoretical approaches to law and seeing that would go beyond simple critique of its pretension of bringing us truth to understand how law might see and unsee, and how it might be seen and unseen? It is also explores devices and practices of visibility, how iconology and iconography have evolved and the relation between the gaze of the law and the blindness of justice.